Model of The Distance Between The Readability of Word Messages on Conventional Signs and Electronic Signs - Budiati, Anik (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Traffic signs are divided into conventional signs and electronic signs. The message conveyed is in the form of a pigtogram and/or electronic message. (Budiati, 2014) compared the legibility distance of letter dimensions on conventional signs, it was found that H=1.032+0.273D with H being the height of the letter and D being the reading distance. (Budiati, 2023), examined the relationship between the driver's reading speed and the number of words and lines in the Variable Message Sigh. This research produces a reading speed of 1.37 words/second. The research was continued to obtain a modeling of the readability distance for conventional and electronic word message signs with the dependent variable (Y) reading distance. Data on reading distance and reading time in the field were analyzed using the SPSS v.23 approach, and the obtained was Y= 2.990 (X1) + 0.009(X2) + 0.001(X3) for conventional signs Y = 3.557 (X1) + 0.440 (X2) + 0.004 (X3), while Based on collineatity the modeling value of reading distance (2) versus reading distance 1 is as follows: Y = 5.463 + 0.513 (X1) + 0.10 (X2) + 0.009 (X3) + 0.004.